Transfer pricing and intangible assets: problem areas in addressing the transfer of intangible assets - Siddle, Robert (Department of Commercial Law, 2016)
In assessing the problems that arise when the practice of transfer pricing is applied to the transfer of intangible asset transfers there are certain areas and nuances that need to be recognized. These include the distinction between economic and legal ownership and the fact that the two concepts, in certain circumstance, are mutually exclusive. Furthermore, the fact that the traditional methods of transfer pricing may not be able to address the unique nature of certain intangibles and that even the more complex methods involving both parties may fall short in situations where the rights and obligations connected to the intangibles assets are not subject to written agreements or accounting standards and procedures. In delving into the interaction of these two fields I will first establish the playing field and the rules, being the practice of transfer pricing, both on the international stage and domestic level. Next it will be necessary to understand the nature of intangible assets as viewed internationally. Upon reviewing the status of intangible assets in the context of transfer pricing I hope to locate the shortcomings caused by the unique characteristic of intangibles and hopefully will be able to suggest some viable options and alternatives.